Cardiac biomarkers in neonatology: BNP/NTproBNP, troponin I/T, CK-MB and myoglobin - a systematic review - Rita P. Teixeira; Ana L. Neves; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2017)
Cardiac biomarkers play a central role in myocardial injury and heart failure in adult patients, but their clinical relevance in neonatology has not been clearly stablished. The aim of this systematic review was to evaluate the recent literature on B-type natriuretic peptide (BNP)/N-terminal-pro-BNP (NTproBNP), troponin I/T, Creatine Kinase-MB (CK-MB) and myoglobin and their relationship with different pathologies of the newborn. A total of 67 articles were included to undergo data extraction, after a first text and abstract analysis and a second full-text analysis, using the PubMed database. Evidence shows that cardiac biomarkers are a useful and fast diagnostic tool with great potential for becoming as important as clinical and echocardiographic findings in pathologies of the heart. BNP/NTproBNP and troponin I/T demonstrated to be the ones with greater value. BNP/NTproBNP is of particular significance in the diagnosis and management of patent ductus arteriosus, as it has a good correlation with diagnosis, treatment and prognosis. Troponin T may be a beneficial additional marker for this disease, correlating with ductal significance and treatment response. Moreover, BNP/NTproBNP can be used, with other clinical and laboratory findings, in the diagnosis and as a guide for treatment in pulmonary hypertension and in the diagnosis and management of cardiac sequela in bronchopulmonary dysplasia. Troponin I/T finds its clinical importance in perinatal asphyxia as a marker of myocardial injury and a reliable indicator of severity and mortality. Further studies with larger cohort populations are needed for stablishing the cutoff values specific for each neonatal pathology allowing its early and proper management.